The problem of local authorities’ measures in preventing illegal domestic waste dumping / Nor Hamalina Abdul Hakim - Abdul Hakim, Nor Hamalina (Faculty of Architecture, Planning and Surveying, 2013)
Increasing population and the problem of improper manner of residents to dump rubbish at improper place and make worsening views especially when residents like to dump rubbish at roadside. The purpose of this study is to know the management of waste dumping at Selangor areas provided by the Local Authorities. A qualitative approach involving interviews, observations and photography were used to gather the necessary primary data, while reference to relevant literature provided me with the much needed secondary data. The information for this study is obtained from the Local Authorities and sampling from a few residents. The study will reveal lack of management for waste dumping from Local Authorities or laziness of residents to dump rubbish at proper place. Illegal dumping domestic waste will be affected to every part of scenery such as when people dump rubbish at river or sea; it will be give bad view to the river.